Campanhas de voz no Brasil: análise na perspectiva da promoção de saúde e prevenção de doenças - Dornelas, Rodrigo (2015)
INTRODUCTION: Voice campaigns are part of the collective actions and connects speech therapists and the strategies of public health policies. OBJECTIVE: to analyze the Voice campaigns promoted by the Brazilian Society of Speech Language Pathology and Audiology (SBFa in portuguese) from the perspective of health promotion and disease prevention. The research was divided into three studies with emphasis in the understanding of construction and development of Voice Campaigns process in the context of health campaigns, health promotion and disease prevention. The first study had as objective resume the historical course of the Voice Campaign and present what is currently proposed; the second analyzed the news reports televised in 2013 about World Voice Day; and the third identified in the winning campaigns from 2005 to 2013 the assumptions involved in health education practices. METHOD: the first study was conducted by a research on the history of the Voice Campaign in Brazil, covering the main challenges encountered. In the second study were analyzed by the Document Analysis technique DA the reports transmitted by the Globo® broadcaster about Voice Campaign. To verify the association between the independent variables (region, schedule turn. professional interviewed, the interview duration and multiprofessionality) the outcome variable (interview approach: general care or disease) was used Fisher's exact test. For the third study, we used the SBFa database of winners of Voice campaigns, with a total of 20 campaigns in eight years. RESULTS: in the first study we consider the importance of the public spheres to appropriate of the theme and to ensure the implementation of actions and that the campaign becomes a permanent daily practice. In the second study it was found that all regions of Brazil were included with news reports. The speech therapist was the professional who addressed the issue in most of these reports and the focus of the interviews were not in the most part of the same nature, promotion or prevention of voice disorder. In the third study it was observed that the Voice campaigns, the distribution of material was the most common action. Over the years we can see a tendency toward unidirectional actions when compared with dialogical actions. CONCLUSION: the Voice campaigns represent a milestone in mobilizing speech therapists which they now have the theme as the object of an educational action. Thus, it is important that this process happens in an accessible way to the population and that participants feel to be contemplated in relation to the various possibilities to exercise the care, reflected in their quality of life